Legal analysis of the implementation of social protest in Colombia: a constitutional and normative vision - Jaraba Fernández, Valentina; Marimón Rodríguez, María Paz; Pereira Ortega, Duanys Liesel (DIXI, 2022)
Social protest is a constitutional right that complements the practical exercise of other rights such as freedom of expression, freedom of assembly and freedom of association, which allows for the existence of democratic societies and their consolidation as a guarantee of the Colombian State. However, in practice it turns out to be contrary to its purpose, due to the fact that the institutions in charge of safeguarding this right attack those who exercise it. By means of the documentary method, based on the search for information and the doctrinal, legal and jurisprudential review, the implementation of social protest in Colombia is evidenced. Due to the covid-19 pandemic, the right to protest was limited. Since the first recorded case of coronavirus was known, the Colombian government adopted a series of measures to prevent, control and mitigate the health effects in the midst of a state of emergency. However, citizens’ discontent with the constant problems of the social environment generated multiple protests as a mechanism of rejection. This allows us to affirm that there is no express regulation on the actions that the public forces should take in the context of social protest.